The relationship of supply chain management, information technology and organizational, performance in manufacturing industeies - Koh, Xiao Qian, 1991-; Norhayati Mohmad Zakwan @ Zakuan, supervisor; Fakulti Pengurusan (2015)
Project Paper (Sarjana Muda Pengurusan (Teknologi)) - Universiti Teknologi Malaysia, 2015